Asymptotic expansions for the sums of independent random variables - Pipiras, V.; Statulevičius, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Пипирас, В. Статулявичус. Асимптотические разложения для сумм независимых случайных величинV. Pipiras, V. Statulevičius. Nepriklausomų atsitiktinių dydžių sumų asimptotiniai išdėstymai